2017
DOI: 10.1097/ijg.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Deformation Parameters Provided by the Corvis ST Tonometer After Trabeculectomy

Abstract: CST is a good choice for measuring IOP, especially when aiming for normalization of IOP after glaucoma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, the optimal model to describe A2 Velocity included IOP-GAT; A2 Velocity is correlated to IOP-G [ 14 , 25 ] largely because corneal movement during its returning phase is faster when IOP-G is high [ 14 , 25 ]. Nonetheless, eye status (coefficient = -0.023 for 3m-post operation) was also included in the model to explain A2 Velocity, which suggests A2 velocity is faster after cataract surgery despite a decrease in IOP-G. Interestingly, in eyes with trabeculectomy [ 28 ] as well as eyes with cataract surgery [ 24 ], A2 velocity quickens after surgery. The first applanation may reflect collagen fiber elasticity, whereas the second applanation may be related to corneal viscoelasticity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the optimal model to describe A2 Velocity included IOP-GAT; A2 Velocity is correlated to IOP-G [ 14 , 25 ] largely because corneal movement during its returning phase is faster when IOP-G is high [ 14 , 25 ]. Nonetheless, eye status (coefficient = -0.023 for 3m-post operation) was also included in the model to explain A2 Velocity, which suggests A2 velocity is faster after cataract surgery despite a decrease in IOP-G. Interestingly, in eyes with trabeculectomy [ 28 ] as well as eyes with cataract surgery [ 24 ], A2 velocity quickens after surgery. The first applanation may reflect collagen fiber elasticity, whereas the second applanation may be related to corneal viscoelasticity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, eye status (coefficient = -0.023 for 3m-post operation) was also included in the model to explain A2 Velocity, which suggests A2 velocity is faster after cataract surgery despite a decrease in IOP-G. Interestingly, in eyes with trabeculectomy [ 28 ] as well as eyes with cataract surgery [ 24 ], A2 velocity quickens after surgery. The first applanation may reflect collagen fiber elasticity, whereas the second applanation may be related to corneal viscoelasticity [ 28 ]. Therefore, we suggest that eye surgery with direct invasion of the anterior chamber may cause viscoelasticity changes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that A1V was significantly higher in eyes treated with prostaglandin analogues (PGAs) than in those treated without PGAs [ 2 ]. Another study reported that A1V increased significantly even after the first week of antiglaucoma surgery [ 20 ]. In some studies on long-term treatment with topical medications, DAHC increased markedly after 2 years, while PDHC increased slightly [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%